Studi Eksperimental Skala Laboratorium Rumah Pengering Kopi Menggunakan Plastik Ultra Violet (UV Solar Dryer) Dengan Mekanisme Konveksi Paksa - Riky Yonerto Runesi; Verdy A. Koehuan; Nurhayati Nurhayati (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2020)
The utilization of solar radiation in the greenhouse effect dryer (ERK) is an alternative to overcome the drying process constraints. The drying process in direct sunlight, which is common in the community, has drawbacks, such as low capacity and takes a long time, and the risk of contamination and disturbance from animals during the drying process. Meanwhile, the quality criteria for coffee beans include physical aspects, taste, and cleanliness as well as uniform and consistent aspects which are largely determined by the treatment at each stage of the production process. The drying process uses ultraviolet plastic (UV solar dryer) to absorb solar radiation and the heat is trapped, then it is used for the drying process of the material. The problem studied is how the performance of the coffee bean drying house through experimental studies using ultraviolet plastic (UV solar dryer) using the forced convection mechanism. The purpose of this study was to determine the efficiency of the coffee bean drying house and the drying rate on the speed of the outflow of air through the exhaust fan. Drying time starts from 11.00 to 15.00 with a total initial coffee weight of 53.37 kg (drying capacity 7.76 kg/m2) and an initial moisture content of 45.5%. From the experimental results, the temperature distribution in the dryer house with an increase in the outflow velocity through the exhaust fan, the air temperature distribution in the dryer house tends to be uniform. However, the variation in flow rate shows the highest coffee bean drying rate at an exit speed of 1.0 m/s, with an efficiency of 9.68% and specific energy consumption of 32799.64 kJ/kg